The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.3354/meps025031
|View full text |Cite
|
Sign up to set email alerts
|

Temperature responses of ribulose bisphosphate carboxylase and photosynthetic capacity in arctic and tropical phytoplankton

Abstract: When assayed near respective in situ temperatures, ribulose blsphosphate carboxylase (RuBPC) exhibits a greater response to increasing temperature in arctic than in tropical phytoplankton. This was also true when the Arrhen~us activation energy (E,) was compared for a range of intermediate temperatures. This difference in temperature response and E, for RuBPC is consistent with the temperature response of photosynthetic capacity, but is contrary to the general observation that coldenvironment ectotherms (organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The high activity of RuBPC compared to PePC and PePCk clearly shows that C3-carboxylation dominated over p-carboxylations. This corresponds to data of Smith & Platt (1985), who showed for Arctic phytoplankton that RuBPC was the only enzyme tightly linked to photosynthetic capacity. For marine phytoplankton, Appleby et al (1980) and Descolas-Gros & Fontugne (1985) observed that RuBPC dominated over the PePC and PePCk.…”
Section: Enzyme Activitiessupporting
confidence: 90%
See 1 more Smart Citation
“…The high activity of RuBPC compared to PePC and PePCk clearly shows that C3-carboxylation dominated over p-carboxylations. This corresponds to data of Smith & Platt (1985), who showed for Arctic phytoplankton that RuBPC was the only enzyme tightly linked to photosynthetic capacity. For marine phytoplankton, Appleby et al (1980) and Descolas-Gros & Fontugne (1985) observed that RuBPC dominated over the PePC and PePCk.…”
Section: Enzyme Activitiessupporting
confidence: 90%
“…After 3 additional minutes of prelncubation, the samples were inoculated with NaHI4CO3 (100 pl, 5 yCi) and incubated at 20°C for 40 min. This temperature is adequate for enzyme activities according to the results of Li et al (1984) for 3 carboxylatlng enzymes in Arctic phytoplankton, and Descoslas-Gros & De Billy (1987) and Smith & Platt (1985) for RuBPC in respectively cultures of Antarctic diatoms and Arctic phytoplankton. The reaction was stopped by the addition of 0.5 m1 6 N HC1.…”
Section: Methodsmentioning
confidence: 95%
“…7A,B). The observation that NR activity in Skeletonema costatum is maximal around 10-15ЊC (Packard et al 1971;Kristiansen 1983;Dohler 1991) and inactivated above 20ЊC (Gao et al 1993(Gao et al , 1997 and the observation that RUBISCO activity is maximal at Ͼ30ЊC (Li et al 1984;Smith and Platt 1985;Descolas-Gros and de Billy 1987) are not yet available and therefore are not included. The linear regression is significant at the P Ͻ 0.001 level.…”
Section: Discussionmentioning
confidence: 99%
“…However, Arctic phytoplankton do not appear to acclimate to cold by increasing Rubisco content per unit pigment biomass 0. C. Smith and Platt 1985).…”
Section: Temperaturementioning
confidence: 99%